2015
DOI: 10.1515/acve-2015-0038
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Troponin-I Concentration In Weaned Calves With Bovine Respiratory Disease

Abstract: The aim of this study was to evaluate the serum cardiac troponin I (cTnI) concentrations in weaned calves with moderate and severe bovine respiratory disease. Eighteen healthy weaned calves (group I), 18 weaned calves with moderate bovine respiratory disease (group II) and 18 weaned calves with severe bovine respiratory disease (group III) were included in the study. Clinical signs and severity of respiratory disease according to clinical index scores were determined. Blood cell counts and cardiac biomarkers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Variations are expected in measuring cTnI concentrations when samples are evaluated with different immunoassays (14). The cTnI level has recently been used for determination of myocardial cell damage in different pathologic conditions such as FMD in lambs (15), traumatic reticuloperitonitis (16), endotoxemia (17), monensin toxicosis (12), theileriosis (7), bovine respiratory disease (18) in calves and cattle, and downer cow syndrome (19). In our study, the serum cTnI concentration of healthy control cow was 0.14 ± 0.04 ng/mL, which is close to and consistent with the findings of Başbuğan et al (13), but does not agree with findings from other studies (1,12,14).…”
Section: Discussionmentioning
confidence: 99%
“…Variations are expected in measuring cTnI concentrations when samples are evaluated with different immunoassays (14). The cTnI level has recently been used for determination of myocardial cell damage in different pathologic conditions such as FMD in lambs (15), traumatic reticuloperitonitis (16), endotoxemia (17), monensin toxicosis (12), theileriosis (7), bovine respiratory disease (18) in calves and cattle, and downer cow syndrome (19). In our study, the serum cTnI concentration of healthy control cow was 0.14 ± 0.04 ng/mL, which is close to and consistent with the findings of Başbuğan et al (13), but does not agree with findings from other studies (1,12,14).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with herpesvirus infections in other animals, most clinical signs after infection were involving the respiratory system according to its host cellular tropism and host restrictive property [1]. However, other clinical signs affecting other organs were reported such as ocular diseases in feline herpesvirus-1 (FHV-1) infection [1], cardiac injuries in calves with bovine herpesvirus-1(BHV-1) infection [23], caulifl ower-like mass on the skin and genital tract in dolphins with bottlenose dolphin herpesvirus (TTHV) infection [24], and abortion with encephalomyelitis in equine herpesvirus-1 (EHV-1) infection [25].…”
Section: Discussionmentioning
confidence: 99%
“…The data of aggravated cardiotoxic effect of tilmicosin with diclofenac sodium treatment (Oda and Derbalah 2018) was supported with our results. The combined use of antibiotics and NSAIDs is recommended to treat the respiratory diseases complex (Lekeux 2007, Guzel et al 2010) but some studies (Mellanby et al 2009, Moammar et al 2010, Hanedan et al 2015 show that also pneumonia may effect in cardiac damage. Hanedan et al (2015) have reported that pneumonia increased the serum cTn-I concentration.…”
Section: Discussionmentioning
confidence: 99%